2004
DOI: 10.1002/adfm.200305181
|View full text |Cite
|
Sign up to set email alerts
|

Singlet and Triplet Exciton Diffusion in a Self‐Organizing Porphyrin Antenna Layer

Abstract: We have studied the photoinduced charge separation in a double layer consisting of a 50 nm thick, discotic antenna layer, i.e., free‐base tetra‐para‐octylphenyl porphyrin (H2TOPP), spin‐coated onto a smooth layer of anatase TiO2 using the electrodeless “flash‐photolysis time‐resolved microwave conductivity” technique (FP‐TRMC). This method enables the investigation of the relationship between the morphology of the antenna layer and the exciton diffusion dynamics. Photons absorbed by the porphyrin result in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 33 publications
1
50
1
Order By: Relevance
“…Kroeze et al reported that free electrons in the conduction band (CB) of the TiO 2 are generated as a result of the photon absorption of an antenna layer (porphyrin dyes). [39] According to the above data analysis, the following mechanism is suggested. Within this 3D TPPS/TiO 2 framework, TPPS absorbs visible light to induce a p-p* transition; the excited-state electrons from the p*-orbital are then readily injected into the d-orbital conduction band (CB) of TiO 2 and subsequently transferred to the TiO 2 surface where they react with molecular oxygen to yield O 2 ·À radicals, which will then be involved in the overall oxidation of CH 3 CHO (Figure 6 and [Equations (1-5)]).…”
Section: à2mentioning
confidence: 99%
“…Kroeze et al reported that free electrons in the conduction band (CB) of the TiO 2 are generated as a result of the photon absorption of an antenna layer (porphyrin dyes). [39] According to the above data analysis, the following mechanism is suggested. Within this 3D TPPS/TiO 2 framework, TPPS absorbs visible light to induce a p-p* transition; the excited-state electrons from the p*-orbital are then readily injected into the d-orbital conduction band (CB) of TiO 2 and subsequently transferred to the TiO 2 surface where they react with molecular oxygen to yield O 2 ·À radicals, which will then be involved in the overall oxidation of CH 3 CHO (Figure 6 and [Equations (1-5)]).…”
Section: à2mentioning
confidence: 99%
“…Keywords: electrochemistry · electron transfer · photochemistry · semiconductors · titanium dioxide case diverse organic dyes (porphyrins, [36][37][38][39][40] phthalocyanines, [41][42][43][44][45] thiacarbocyanine dyes, [46,47] various natural dyes [48][49][50][51][52][53][54][55][56] ) and metal complexes [49] undergo photoexcitation with visible light and inject electrons into the conduction band ( Figure 1b). Chemisorption of chromogenic molecules onto the TiO 2 surface results in formation of ligand-to-metal or metal-to-metal charge transfer (LMCT and MMCT, respectively; more precisely referred to as ligand-to-particle or metal-to-particle charge transfer; LPCT and MPCT) involving surface Ti IV ions and surface-bound ligands or transition-metal complexes, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[28,37,38] An inspiration for light-harvesting molecules and antenna systems capable of titania photosensitization comes from various biosystems. [39] There are numerous trials of solar-cell construction which are based on biomolecules and supramolecular systems; for instance, porphyrins, [40][41][42][43][44] phtalocyanines, [45] thiocarbocyanine dyes, [46,47] natural dyes, [48][49][50][51][52][53][54] etc. In every case, the redox-active molecules supply electrons from their excited states.…”
Section: Introductionmentioning
confidence: 99%